Charting light harvesting in purple bacteria in vivo - Romain Rouxel; Julian Lüttig; Michael R. Jones; Donatas Zigmantas (Proceedings of the National Academy of Sciences, 2026)
Understanding the remarkable quantum efficiency of solar energy collection in phototrophic bacteria requires a clear description of the functional connectivity between the individual complexes comprising the photosynthetic apparatus. While significant progress has been made since the 1980s in understanding energy transfer dynamics within isolated complexes, information about intercomplex processes in intact cells is still sparse. One reason is the great complexity of intact systems that leads to highly congested spectra, especially at room temperature. Two-dimensional electronic spectroscopy (2DES) is a method that is well suited to discriminating between different subsystems and disentangling their responses, since the excitation energy is resolved along the “second dimension” of the spectra. However, 2DES on intact photosynthetic systems such as whole bacterial cells is challenging due to the high scattering properties of such samples. With a 2DES setup designed to reduce scattering, we were able to overcome these limitations. Here, we present physiological temperature measurements on intact cells of the purple photosynthetic bacterium Rhodobacter sphaeroides , which enabled us to fully map the energy transfer processes in an intact photosynthetic unit with femtosecond resolution, from the initial light-harvesting steps in the antenna complexes LH2 and LH1 through to arrival of the excitation to the reaction center. In particular, we observe the appearance of a clear signature of charge separation in the reaction center as a strong electrochromic band-shift signal. Through a global analysis approach, we extract the effective time constants for all these processes and expand the existing picture of how bacterial light harvesting works in vivo.